Deskripsi Kemampuan Eksplorasi Mahasiswa Dalam Pemecahan Masalah Matematis - Lestari, Amelia; Anggun Nopela, Lola; Lorenza, Sintia (JPT : Jurnal Pendidikan Tematik, 2020)
The purpose of this study was to explore understanding and mastery of the material through exploratory descriptions of students in solving mathematical problems. The method used is descriptive qualitative exploratory with research subjects, namely three students (high, medium and low ability) at the Mathematics tadris, Bengkulu State Islamic Institute (IAIN) who are taking the Calculus 2 course.The main instrument is the researcher himself, while the auxiliary instrument in the form of two problem solving questions from the Derivative Application material that has been validated by previous research and interview guidelines. The data analysis procedure was carried out through a qualitative analysis of the written test results. The results of students' exploratory ability in solving mathematical problems, the average achievement of the assessment is in a good category on the indicator of mathematical exploration ability in the form of mathematically formulating situations and using mathematical concepts. While the indicators of compiling plans and solving mathematical problems are in the moderate category for low students (MR) and in the good category for students with moderate (MS) and high (MT) abilities.